Performance evaluation of μDMFCs based on porous-silicon electrodes and methanol modification. (1st February 2020) - Yang, Chii-Rong; Lu, Chang-Wei; Fu, Pin-Chi; Cheng, Chia; Chiou, Yuang-Cherng; Lee, Rong-Tsong; Tseng, Shih-Feng
Abstract: This study aims to develop micro direct methanol fuel cells (μDMFCs) incorporating flow-field plates with porous-silicon diffusion layers to form two types of bipolar electrodes, one with a hill-like structure (HLS) and the other with a through-hole silicon (THS) structure. Carbon nanotubes are grown on the surface diffusion layers to serve as catalyst supports. Furthermore, methanol fuel is modified by adding SDSS surfactant with the intent of enhancing its wettability and ability of CO2 removal for preventing CO2 coverage of catalyst layer. The experimental results indicate that the maximum power density of this HLS-THS cell (0.186 mW/cm 2 ) is 4.4 times higher than that of the cell with conventional CP-CP (carbon paper) electrodes. The μDMFCs without SDSS has the highest output voltage at 0.66 V, yet the value linearly decreases to 0 V in only 5.5 h. The μDMFCs with 0.1% SDSS can maintain an average output voltage of 0.45 V for 8 h before the value decreases to approximately 0 V as a result of fuel depletion. Although the output voltage of the μDMFCs with 0.5% SDSS remains steadily at 0.425 V, the voltage decreases to negative values after 7 h because of fuel depletion and crossover. Highlights: The performance of μDMFCs with various diffusion structures is explored. The flow-field plates are incorporated with porous-silicon diffusion layers. Carbon nanotubes are grown on the diffusion layers to serve as catalyst supports. The modified methanol fuel can enhance its wettability and remove CO2 bubbles.